Study on Prediction of Disaster Risk Caused by Heavy Rain in Shingjin, Songxian County - Shi Xin (E3S Web of Conferences)
In recent years, extreme rainstorm weather occurred frequently in our country, which caused mine safety accidents are also increasing, resulting in huge economic losses and casualties. Based on the analysis of the “three zones” formed by the mining face of Shanjin Mine in Songxian County and the characteristics of the surface, the risk points caused by heavy rain in the whole mine were studied, and the key disaster areas were determined according to different levels of heavy rain. The borehole TV method and isotope tracer method were used to probe the key areas, and it was concluded that the rain generated by heavy rain would not cause water inrush accidents in the mine. In the ArcGIS environment, the regional geological hazard assessment index of Songxian County was calculated by superimposing the normalized results of susceptibility and the normalized results of accumulated monthly rainfall from 2013 to 2023, and it was determined that the Songxian Shan Gold Mine was in the low risk area caused by heavy rain.